Parameter optimization and test of digging-shaking-pulling ginger harvesting device based on DEM-MBD coupled simulation - Wang, Fangyan; Tian, Fulun; Wang, Wenlong; Wang, Renchao; Zhang, Huan; Wang, Xin (International Journal of Agricultural and Biological Engineering, 2026)
The primary objective of this study was to address the challenges associated with the harvesting of ginger, namely the large resistance to digging, the high damage rate, and the high impurity rate of the harvested ginger. To this end, a digging-shaking-pulling ginger harvesting device (DSPGHD) was designed and optimized. The device was then analyzed in accordance with agronomic requirements for ginger planting and harvesting. This analysis involved the examination of interactions between ginger, soil, and mechanisms at each stage of the harvesting process. The study determined the key factors affecting the harvesting indices, including the initial angle of the clearing bar (IACB) φ, the length of the clearing bar (LCB) l2, and the frequency of shaking (FS) f. The coupled EDEM-RecurDyn simulation system was established, and the key factors were tested with the forward resistance, the ginger force, and the effect of the soil flow as the test indices. A single-factor test was conducted, and the test result data was analyzed to determine the factor influence law. The field orthogonal test was then designed to optimize the parameter combinations of the device, and the response surface analysis and multi-objective optimization method were used to obtain better parameter combinations of the evaluation indices of ginger harvesting. These were as follows: the IACB was 8.7°, the LCB was 256 mm, and the FS was 4.24 Hz. The sizes of the test indices were as follows: the forward resistance was 1526 N, the damage rate was 4.57%, and the impurity rate was 3.74%. The DEM-MBD model developed in this study has the capacity to investigate the interactions between the primary factors of the DSPGHD and ginger-soil. It can optimize the geometric structure of the machine and provide a theoretical foundation for field trials. The optimized results from the field orthogonal test can satisfy the agronomic requirements and use requirements of ginger harvesting, and reduce the input of labor. Keywords: DEM-MBD coupling, ginger, harvesting machinery, soil, digging and shaking and pulling DOI: 10.25165/j.ijabe.20261901.9937 Citation: Wang F Y, Tian F L, Wang W L, Wang R C, Zhang H, Wang X. Parameter optimization and test of digging-shaking-pulling ginger harvesting device based on DEM-MBD coupled simulation. Int J Agric & Biol Eng, 2026; 19(1): 97–107.